Democratization of Village Autonomy in the Construction of Indonesian Administrative Law: Is It Possible? - Hariyanto, Hariyanto; Yeyeng, Andi Tenri; Kapugu, Betsy Anggreini; Arowosaiye, Yusuf Ibrahim; Tajuddin, Muhammad Saleh (Jurnal Media Hukum, 2025)
This article explores the potential for democratizing village autonomy within the Indonesian administrative law framework. Although Law No. 6 of 2014 and Law No. 3 of 2024 have granted formal recognition of village self-governance, significant challenges persist, including elite domination, corruption, limited community participation, and weak institutional capacity. Through a normative legal and comparative approach, this study examines the village autonomy experiences of India and the Philippines to identify best practices applicable to Indonesia. Findings indicate that democratization of village autonomy is achievable when supported by legal reform, institutional strengthening, transparent governance, and active citizen engagement. Democratization must go beyond procedural aspects like elections and include cultural adaptation, community empowerment, and the establishment of accountability mechanisms to prevent elite capture. Effective collaboration between central, regional, and village governments is essential to ensure participatory governance that aligns with local needs. Lessons from international cases underline the importance of community-driven planning and legally mandated public participation to achieve sustainable village development. This study concludes that democratizing village autonomy can significantly contribute to inclusive and resilient governance in Indonesia if systemic barriers are addressed comprehensively.